607 Long-term results of neoadjuvant dose-dense platinum-based chemotherapy in patients with locally advanced cervical cancer. (14th December 2020) - Smirnova, Olga; Ulrikh, Elena; Abramova, Alina; Yakovleva, Maria; Petrova, Anna; Mikaya, Nikolay; Lavrinovich, Olga; Bondarev, Nikolay; Urmancheeva, Adel; Berlev, Igor
Abstract : Introduction/Background: In our study, we evaluated the long-term results of neoadjuvant dose-dense platinum-based chemotherapy in patients with locally advanced cervical cancer FIGO IB2, IIB stage. Methodology: A cohort of 119 consecutive patients with median age of 43 (range 27–68) years was studied. All patients had verified locally-advanced (cT1B 2Nx, 0M0; cT2B Nx, 0M0) cervical cancer and received 3 dose-dense intravenous neoadjuvant AP (cisplatin 75 mg/m2, doxorubicin 35 mg/m2; n=75) or TP (cisplatin 60 mg/m2 and paclitaxel 60 mg/m2; n=30) chemotherapy cycles. Results: The median follow-up was 28 (4 - 48) months for AP and 17 (3 - 30) months for TP group, accordingly. The overall survival rates in FIGO IB2 stage for AP and TP groups were 100%. For FIGO IIB stage the overall survival rate in AP group was 94%, in TP group - 97%. The disease-free survival rate in FIGO IB2 stage for AP group was 78%, for TP group - 100%. For FIGO IIB stage the disease-free survival rate in the AP group was 87%, in TP group - 100%. Conclusion: The dose-intensive chemotherapy is an effective treatment modality for locally-advanced cervical cancer and may be a feasible alternative for standard treatment approach. It deserves further study in larger patient cohort with evaluation of the long-term results.